2019
DOI: 10.7759/cureus.6083
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Anti-glutamic Acid Decarboxylase-65 Antibody Positive Stiff Person Syndrome Presenting Initially as Acute Peripheral Vestibulopathy, Leading to Delayed Diagnosis After Multiple Hospitalizations

Abstract: Stiff person syndrome (SPS), with a prevalence of one to two per million, is an extremely rare neurological condition that is characterized by axial muscle stiffness and rigidity along with intermittent painful muscle spasms. It is often associated with psychiatric co-morbidities such as anxiety and depression. The pathophysiology, although poorly understood, is widely believed to be autoimmune in nature due to the association of anti-glutamic acid decarboxylase-65 (anti-GAD 65) antibodies with this condition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Table 1 shows that from 29 studies on breast cancer, six SPSSD subtypes, including classic SPS ( 21 , 30 , 37 47 , 50 , 63 , 64 ), SLS ( 57 , 58 , 65 ), paraneoplastic cerebellar degeneration ( 59 ), subacute sensory neuronopathy, subacute cerebellar degeneration ( 60 ), and PERM ( 61 ), among which classic SPS is the major SPSSD subtype, were found to be involved. Patients with breast cancer and PSSD were determined to have other carcinomas, such as colon cancer, non-Hodgkin lymphoma, thymoma and lymphoma, and malignant melanoma ( 21 , 34 , 39 , 41 ). Furthermore, patients with breast cancer and SPSSD were found to have other diseases, including autoimmune diseases, such as paraneoplastic encephalomyelitis, type 1 diabetes, thyroid disease, pernicious anemia, vertigo, psoriasis, thyroid disease, rheumatoid arthritis, sarcoidosis, mixed connective disease, limbic encephalitis, myelopathy, HIV, and ischemic cardiomyopathy ( 21 , 34 , 41 , 45 , 58 , 59 , 65 ).…”
Section: Clinical Characteristics Of Malignant Tumor-related Spssdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows that from 29 studies on breast cancer, six SPSSD subtypes, including classic SPS ( 21 , 30 , 37 47 , 50 , 63 , 64 ), SLS ( 57 , 58 , 65 ), paraneoplastic cerebellar degeneration ( 59 ), subacute sensory neuronopathy, subacute cerebellar degeneration ( 60 ), and PERM ( 61 ), among which classic SPS is the major SPSSD subtype, were found to be involved. Patients with breast cancer and PSSD were determined to have other carcinomas, such as colon cancer, non-Hodgkin lymphoma, thymoma and lymphoma, and malignant melanoma ( 21 , 34 , 39 , 41 ). Furthermore, patients with breast cancer and SPSSD were found to have other diseases, including autoimmune diseases, such as paraneoplastic encephalomyelitis, type 1 diabetes, thyroid disease, pernicious anemia, vertigo, psoriasis, thyroid disease, rheumatoid arthritis, sarcoidosis, mixed connective disease, limbic encephalitis, myelopathy, HIV, and ischemic cardiomyopathy ( 21 , 34 , 41 , 45 , 58 , 59 , 65 ).…”
Section: Clinical Characteristics Of Malignant Tumor-related Spssdsmentioning
confidence: 99%
“…The major SPSSD subtype is classic SPS ( 11 , 68 , 69 , 73 , 77 , 80 , 92 – 98 , 134 , 135 ), followed by SPS with myasthenia gravis ( 21 25 , 29 , 31 , 34 36 , 86 , 89 , 90 , 135 , 136 ), PERM ( 91 ), SLS ( 57 ), progressive dizziness and unstable gait ( 87 ), and NMDAR-SPS ( 9 ), as shown in Table 5 . Moreover, the major carcinoma associated with SPSSD subtypes is breast cancer ( 21 , 39 , 42 , 47 , 50 , 51 , 56 , 57 , 137 ), followed by thymoma ( 11 , 80 , 91 98 , 104 106 , 134 , 135 ), lymphoma ( 77 , 80 ), lung cancer ( 68 , 69 , 73 ), and other carcinomas ( 21 25 , 29 , 31 , 34 36 , 86 , 89 , 90 , 135 , 136 ).…”
Section: Possible Mechanisms Of Paraneoplastic Spssdmentioning
confidence: 99%
“…The second disease is stiff-person syndrome (SPS), often seen accompanied by thymomas and breast cancer. SPS is a rare neurological disease with 1-2 cases/million [72,73], and is characterized by rigidity and spasm of skeletal muscles in limbs and trunks. Patients showed increased sensitivity to stimuli, such as noise and emotional perturbation [74].…”
Section: Autoimmune Disorders' Attack On the Gaba-ergic System Correlates With Neurological Diseases And Cancersmentioning
confidence: 99%
“…One study found high GAD antibody levels in 2.8% of patients with epilepsy, 5 and another study found elevated GAD antibody levels in patients with temporal lobe and generalized epilepsy 6 . Because approximately 60%–80% of SPS patients are positive for anti‐GAD antibodies, clinical diagnosis of SPS may be delayed in patients with underlying seizure disorder 7 . As has been shown in SPS with auditory stimuli causing spells, musicogenic reflex seizures have been described in epilepsy patients with anti‐GAD antibodies, further complicating differentiation between SPS and epilepsy 8 …”
Section: Introductionmentioning
confidence: 99%
“…6 Because approximately 60%-80% of SPS patients are positive for anti-GAD antibodies, clinical diagnosis of SPS may be delayed in patients with underlying seizure disorder. 7 As has been shown in SPS with auditory stimuli causing spells, musicogenic reflex seizures have been described in epilepsy patients with anti-GAD antibodies, further complicating differentiation between…”
mentioning
confidence: 99%